2004
DOI: 10.3200/bmed.29.4.167-174
|View full text |Cite
|
Sign up to set email alerts
|

The Feeling of Fatigue—Fatigue Severity by Unidimensional Versus Composite Questionnaires

Abstract: The authors' purpose in this study was to compare the perception of fatigue severity as measured by different fatigue questionnaires. The authors evaluated 3 groups of patients in a cross-sectional study: chronic fatigue syndrome (CFS, n = 20), non-CFS fatigue (n = 20), and familial Mediterranean fever (FMF n = 25). In addition, the authors tracked 7 patients with CFS longitudinally for severity of fatigue. The severity of fatigue-related symptoms was assessed with 2 questionnaires: the unidimensional Chalder'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Although the FIS was developed for use in clinical populations (e.g., MS and hypertensive patients) [43,45], it has also been used to evaluate fatigue in healthy community controls (e.g., Refs. [3,46]) and university students [6]. In this study, the three subscales and total scale had Cronbach's alpha ranging from .90 to .97.…”
Section: Methodsmentioning
confidence: 99%
“…Although the FIS was developed for use in clinical populations (e.g., MS and hypertensive patients) [43,45], it has also been used to evaluate fatigue in healthy community controls (e.g., Refs. [3,46]) and university students [6]. In this study, the three subscales and total scale had Cronbach's alpha ranging from .90 to .97.…”
Section: Methodsmentioning
confidence: 99%
“…29 In a recent clinical study, Naschitz et al found strong correlations between an unidimensional fatigue scale and scales measuring the cognitive, physical, and social impact of fatigue. 34 The validity and reliability of self-reported work factors have been explored and discussed by several authors. [35][36][37] Some authors have found high correlations 35 and others have found fair or modest correlations 36 37 between ''objective'' and self-reported information on psychosocial work environment.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Internal consistency for the scale is high with a Cronbach alpha of 0.98 (Fisk et al, 1994). The FIS has previously been used to evaluate fatigue in healthy adults (LaChapelle and Finlayson, 1998;Naschitz et al, 2004).…”
Section: Methodsmentioning
confidence: 99%